Comparison of Chemoreceptive Abilities of the Hydrothermal Shrimp Mirocaris fortunata and the Coastal Shrimp Palaemon elegans. (20th June 2018) - Machon, Julia; Lucas, Philippe; Ravaux, Juliette; Zbinden, Magali
Abstract: Chemoreception might play an important role for endemic shrimp that inhabit deep and dark hydrothermal vents to find food sources and to locate active edifices that release specific chemicals. We compared the chemosensory abilities of the hydrothermal shrimp Mirocaris fortunata and the coastal related species, Palaemon elegans . The detection of diverse ecologically relevant chemical stimuli by the antennal appendages was measured with electroantennography. The 2 species can detect food-related odor and sulfide, a short-distance stimulus, via both their antennae and antennules. Neither iron nor manganese, considered as long-distance stimuli, was detected by the antennal appendages. Investigation of the ultrastructure of aesthetasc sensilla revealed no specific features of the hydrothermal species regarding innervation by olfactory sensory neurons. Pore-like structures occurring in the aesthetasc cuticle and dense bacterial covering seem to be unique to hydrothermal species, but their potential link to chemoreception remains elusive.